(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this article, The effect of sowing seeds in the norms 4, 5, 6 mln of grain/ha on the growth and development of new varieties of oilseed flax has been studied. It has been proven that the growing period lasted 2-3 days faster in the option where 4 million seeds were used according to the seed sowing norms, compared to the option where the sowing rate was increased to 6 million seeds per hectare. It has been proven that the Russian Fliz variety, which gave good results on the same level as the Bahorikor(st) variety, is well adapted to the climatic conditions of Uzbekistan and prevailed over other varieties.